Installation of NEOPTOLEMOS, the new sum spectrometer for cross section measurements of capture reactions at the ΤANDEM Accelerator Laboratory of NCSR “Demokritos” - Lagaki, V.; Michalopoulou-Petropoulou, V.; Axiotis, M.; Foteinou, V.; Lagoyannis, A.; Provatas, G.; Harrisopulos, S. (HNPS Advances in Nuclear Physics, 2019)
Cross-section measurements of capture reactions are of key importance in understanding the contribution of the uncertainties of nuclear properties, such as the nucleon-nucleus potential and the nuclear level densities, entering in astrophysics abundance calculations. During the recent years, the Nuclear Astrophysics group of NCSR “Demokritos” has been conducting angle-integrated cross-section measurements using a large-volume NaI(Tl) detector installed at the Dynamitron Tandem Laboratory of the University of Bochum in Germany. Thanks to LIBRA funds a brand new cylindrically shaped NaI(Tl) detector, coined NEOPTOLEMOS, was acquired that is axially segmented in two, covering a solid angle of almost 4π for γ rays emitted at its center.